Interfacial modification on polyhydroxyalkanoates/starch blend by grafting ​in-situ. (15th October 2017) - Xu, Pengwu; Zeng, Qingtao; Cao, Ying; Ma, Piming; Dong, Weifu; Chen, Mingqing
Highlights: Interfacial bonding was in situ created by radical grafting leading to smaller adhesion factor. Compatibility and interfacial adhesion between PHAs and starch were considerably improved. A simple way to make blends with low-cost and good performance was provided. Abstract: The interfacial adhesion between polyhydroxyalkanoates (PHAs) and native starch is poor. To improve the interfacial adhesion, PHAs were in-situ grafted onto starch using dicumyl peroxide (DCP) as a free radical initiator. The grafting reaction was carefully characterized and confirmed by gel analysis and Fourier transform infrared spectroscopy (FT-IR). The gel yield of the PHAs/starch/DCP blend increased with the DCP concentration up to 2 wt%. Meanwhile, obvious plastic deformation (stretched fibrils) was observed at the interface in the PHAs/starch/DCP blend in comparison with complete interfacial debonding in the PHAs/starch physical blend. The improved interfacial adhesion after grafting was further confirmed by a reduction in adhesion factor ( Af ) obtained from dynamic mechanical analysis (DMA). The mechanical strength and the crystallization rate of the PHAs were deteriorated after incorporation of starch, and were backed up by the interfacial improvement. A linear relationship between the mechanical properties and the gel yield was discovered. In addition, the PHAs/starch/DCP blend exhibited higher decomposition active energy ( Ea ) and thus better thermal stability in comparison with the PHAs and the PHAs/starch physical blend. Therefore, this study provides a simple route to utilize low-cost starch as a component in biopolymer blend.